Fostering Learner Autonomy in Vietnamese Higher Education: What Factors to Be Considered? - Cao, Dung Thi Phuong; Pho, Phuong Dzung (Center of Language Development, Institut Agama Islam Negeri Madura, 2024)
Learner autonomy is widely recognized as a significant goal for tertiary education in enabling learners to become lifelong learners. To achieve this goal, it is crucial to identify what factors support or impede learner autonomy. This study, therefore, aims to explore influencing factors by collecting data from 420 English majors at a university in the south of Vietnam, using questionnaire surveys and focus group interviews. Its results show that motivation and teachers’ teaching styles and requirements are the two most influential factors, representing internal and external elements, respectively. Internal factors are found to be more influential than external ones, with eight out of nine identified as very influential (i.e., motivation, learning attitudes, knowledge of the subjects, language proficiency, learning styles, learning goals, preferences for self-study, learning methods/techniques). Family expectation emerged as a new external element contributing to learner autonomy. Discussion about the influence level and suggestions for facilitating learner autonomy are presented.